The Influence Of Beauty Influencer Marketing And Viral Marketing On Purchase Intention: The Mediating Role Of Brand Trust In The Originote Skincare Products - Setya Rahmalida, Hanti; Susan, Marcellia (Publisher Cv. Inara, 2025)
This study aims to examine the impact of beauty influencer marketing and viral marketing on purchase intention, with brand trust as a mediating variable in the context of the skincare brand The Originote. The use of influencer and viral marketing strategies has become increasingly popular among brand owners as a means to foster consumer trust and drive purchasing behaviour. A quantitative approach with an explanatory research design was adopted. Primary data were collected through an online questionnaire distributed to 160 male and female respondents aged 20 and above, all of whom are active social media users familiar with the influencers Tasya Farasya and Dokter Detektif. The data were analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method via SmartPLS 4.0 software. The findings reveal that both beauty influencer marketing and viral marketing have a positive and significant influence on brand trust and purchase intention. in addition, brand trust was found to significantly mediate the relationship between both types of marketing and purchase intention.